1 2 3 (A( 1 2 3
2 2 (B) 1 2
1 1 3 3 5 7 )C( 7 1 5
A x 2 y 3z 0 x 2 y 3z 0
C -
-
-
( -
aij a a
a
. . .
. . . .
.
am1
a1n
. amn
n m
n
1
m
n
m=n ann
a
n×m
a
a
a
A=0
11 2 5 A B 2 3 1 2
1 5 B 3 2
1 2 A 2 1
B A C B A A+B=B+A A+(B+C)=(A+B)+C k
k(A+B)=kA+kB=(A+B)k A+D=B
2
D
a11
a12
b11 m b21 ... a1m . a11b11 a12b12 ... a1m bm1 a1k bk1 k 1 bm1
B B
A
A
B A
B A
A B C B A A(B+C)=AB+AC (A+B)C=AC+BC A(B C)=(A B)C AB≠BA
B=0
AB=0
A=0 B=C
3
AB=AC
i>j
aij=
A i<j
aij=
A=diag(a , a , a , …, ann) a = a = a = …= ann=k k=1 n
1 0 15 0 0 0
A
B
0 1 0 0 0
0 0 1 0 0
0 0 0 1 0
0 0 0 0 1
1 0 0 13 0 1 0 0 0 1
1 0 12 0 1
AB=BA=1
B A B=A-
m×n AT
n×m
A 4
A
1 3 AT 2 5 2 1
k
1 2 2 A 3 5 1
BT AT
B A
A
k AT k AT
A BT AT BT
A BT AT BT
A
T T
A=AT
A
A A
A
A
a11 a12 a11 a22 a12 a21 a21 a22
5
a11 a12 a21 a22 a31 a32
a13 a a23 a11 22 a32 a33
a23 a a a a a12 21 23 a13 21 22 a33 a31 a33 a31 a32
a11 a12 a21 a22 a31 a32
a13 a a23 a21 12 a32 a33
a13 a a a a a22 11 13 a23 11 12 a33 a31 a33 a31 a32
a11 a12 a21 a22 a31 a32
a13 a a23 a31 12 a22 a33
a13 a a a a a32 11 13 a33 11 12 a23 a21 a23 a21 a22
aij
aij
n
A aij
a11 a21 a31 a 12 ... ... adjoint A adjA a13 ... ... ... ... ... a1n ... ... a b d b adj( A) A c d c a b22 b32 b11 b21 b31 b B b12 b22 b32 adj( B) 21 b31 b 13 b23 b33 b 21 b 31
b23 b33 b23 b33 b22 b32
b12
b13
b32 b33 b11 b13
b31 b33 b b 11 12 b31 b32
6
b12 b22 b11
b21 b 11 b21
b13 b23 b13 b23 b12 b22
... an1 ... ... ... ... ... ... ... ann
2 2 2 3 4 4 4 4 5 5 5 6